The Influence of Transformational Leadership on Employee Performance in the Modern Business Sector - Sabastian Bamboo Keyza Sinaga (Patua : Journal of Business Administration and Management, 2024)
This study aims to analyze the influence of transformational leadership on employee performance in the modern business sector. In facing the increasingly complex and competitive business environment, leadership plays a crucial role in improving human resource performance. This study employed a quantitative approach with an associative method. Data were collected through questionnaires distributed to 100 respondents, who were employees in the modern business sector, using simple random sampling. Data analysis was performed using simple linear regression with the aid of statistical software. The results showed that transformational leadership had a positive and significant effect on employee performance. This was evidenced by a significance value less than 0.05 and a positive regression coefficient. Effective transformational leadership can increase employee motivation, commitment, and productivity, thus impacting the quality and quantity of work. In addition, this leadership style also creates an innovative and conducive work environment. Thus, it can be concluded that transformational leadership is an important factor in improving employee performance in the modern business sector. This research is expected to contribute to the development of human resource management science and serve as a reference for organizations in implementing effective leadership strategies.